Comparative Susceptibility of Different Cell Cultures and Chicken Embryo Organ Cultures to Infectious Bursal Disease Virus of Poultry - Salman Akbar Malik, Khalid Naeem Khwaja, Shazia Mannan, Muhammad Ibrahim (Recent Research in Science and Technology, 2009)
Infectious bursal disease (IBD) is an acute highly contagious viral infection of young chickens often resulting in immunosuppression. Inactivated vaccines play significant role in protection against IBD. Mammalian cell lines could be used for producing such vaccines. In present study twenty-five, local strains of IBD virus were inoculated into chicken embryo bursa cell culture, liver cell culture, kidney cell culture, fibroblast cell culture and Vero cell lines for cytopathic effect. Moreover comparative susceptibility of chicken embryo bursa organ, embryo liver organ and embryo kidney organ cultures, to infectious bursal disease virus were studied. Chicken embryo bursa cell line was found to be most susceptible (90%) followed by Vero cell lines (70%), fibroblast cell lines (65%), kidney cell lines (50%) and liver cell lines (45%). While chicken embryo bursa organ culture gave maximum cytopathic effect (80%) followed by chicken embryo liver (60%) and kidney organ (45%). From these studies it is concluded that after bursa cell lines, Vero cell lines gave maximum cytopathic effect yielding high number of virus particles and are easy to maintain. Thus Vero cell lines can be used to produce infectious bursal disease vaccines using local isolates.